2020
DOI: 10.1371/journal.pone.0228775
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci associated with nitrogen use efficiency in winter wheat

Abstract: Maintaining winter wheat (Triticum aestivum L.) productivity with more efficient nitrogen (N) management will enable growers to increase profitability and reduce the negative environmental impacts associated with nitrogen loss. Wheat breeders would therefore benefit greatly from the identification and application of genetic markers associated with nitrogen use efficiency (NUE). To investigate the genetics underlying N response, two bi-parental mapping populations were developed and grown in four site-seasons u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 89 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…QTL detected in both management systems would be ideal for developing improved wheat germplasm using marker-assisted breeding irrespective of management system, while those QTL detected in the conventional (high-N) or organic (low-N) managements should be considered in their respective managements. Several studies have reported similar results in diverse crops, including wheat [ 62 , 63 , 64 , 65 , 66 ], rice [ 67 , 68 ], barley [ 69 ], sorghum [ 70 ], and potato [ 71 ]. Using a doubled haploid winter wheat mapping population evaluated at two N fertilizer treatments under field conditions, An et al [ 64 ] detected a total of 17 QTL associated with different traits under low-N (9) and high-N (8), but none were detected in both N treatments.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…QTL detected in both management systems would be ideal for developing improved wheat germplasm using marker-assisted breeding irrespective of management system, while those QTL detected in the conventional (high-N) or organic (low-N) managements should be considered in their respective managements. Several studies have reported similar results in diverse crops, including wheat [ 62 , 63 , 64 , 65 , 66 ], rice [ 67 , 68 ], barley [ 69 ], sorghum [ 70 ], and potato [ 71 ]. Using a doubled haploid winter wheat mapping population evaluated at two N fertilizer treatments under field conditions, An et al [ 64 ] detected a total of 17 QTL associated with different traits under low-N (9) and high-N (8), but none were detected in both N treatments.…”
Section: Discussionmentioning
confidence: 87%
“…The closest QTL detected in this study were QFlt.dms-5A.1 in the CAB population and both QFlt.dms-5A.2 and QMat.dms-5A.2 in the ACG population ( Figure 3 ), but there is a ~4.6 Mb interval between them. Although identification of QTL conserved across multiple genetic backgrounds is one of the prerequisites for marker-assisted selection, most QTL reported in the literature are population (genetic background) specific [ 37 , 58 , 59 , 60 , 61 , 62 ], which restricts their application for predicting phenotypic performance across diverse genetic backgrounds. Brasier et al [ 62 ] evaluated two biparental winter wheat mapping populations derived from a cross between two high NUE parents and a shared common low NUE parent for 11 traits.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of QTLs associated with nitrogen uptake, utilization, and nitrogen use efficiency have been detected in different cereal crop species (Agrama et al, 1999;Gallais and Hirel, 2004;Ribaut et al, 2007;Fontaine et al, 2009;Wei et al, 2012;Hu et al, 2015;Sandhu et al, 2015;Li et al, 2017;Zhou et al, 2017;Pozzo et al, 2018;Van Deynze et al, 2018;Zhang et al, 2019;Brasier et al, 2020). To the best of our knowledge, none of the identified genomic regions have been deployed in the marker-assisted introgression and pyramiding program.…”
Section: Introductionmentioning
confidence: 99%
“…The NUE, is a complex trait governed by several genes and is largely influenced by the environment [17].To know the position, location, numbers, effects and interaction of loci controlling the traits, quantitative trait loci (QTL) mapping is the best way and can be used as one of the selection strategies. In several studies, QTLs for NUE and its component traits in wheat have been mapped under different agronomic conditions, including low N (LN) level/optimum N level/high N (HN) levels)in the field or under hydroponic culture or in pots [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Most of these studies have been done on winter wheat, and there is a lack of information on important genomic regions governing the NUE in Indian spring wheat germplasm.Moreover, the majority of these studies have focused on QTL analyses for agronomic traits or biochemical enzymes like GS and GDH involved in N assimilation as candidate genes under varying levels of N application in wheat [22][23][24]32].…”
Section: Introductionmentioning
confidence: 99%